Analysis of clinical and functional outcomes of ankle fracture treatment - Santos, Tiago Viriato; Fonseca, Lucas Buri dos Anjos (Journal of the Foot & Ankle, 2025)
Objective: Analyze the clinical and functional outcomes of conservative and surgical treatment of ankle fractures in adults, considering postoperative complications, recovery time, need for reinterventions, quality of reduction, and patient satisfaction. Methods: This study conducted an integrative literature review, searching PubMed, Scopus, Web of Science, Embase, and SciELO databases for publications between 2014 and 2024. Fifty-two articles were initially identified, and after applying the inclusion criteria, six were selected for analysis. The main outcomes evaluated were complication rates, recovery time, quality of reduction, and patient satisfaction. Results: The results indicated that surgical treatment, especially in unstable fractures, favors anatomical reduction and faster recovery, but presents a higher risk of postoperative complications, such as infection and fixation failure. Conservative treatment, although associated with slower recovery and risk of addictive consolidation, showed a lower incidence of serious adverse events. Conclusion: The results presented herein should be interpreted as a preliminary synthesis, useful for guiding clinical practice, but insufficient for generalization. The therapeutic decision for ankle fractures should remain individualized, based on the type of fracture, the patient’s clinical profile, and the team’s experience, with active patient involvement in the decision-making process. Level of Evidence II; Review.